Consumers’ Attitudes Towards Prawn Consumption in Bangladesh: An Investigation on Perceived Value and Willingness-to-Pay - Md Taj Uddin; Sima Roy; Aurup Ratan Dhar (Fishes, 2024)
This study assessed consumer preferences and consumption patterns for prawns in Bangladesh, underscoring the economic and nutritional significance of prawns in the local diet. A total of 120 respondents were interviewed following a random sampling technique from four districts. The data analysis employed descriptive statistics alongside mathematical and statistical methods. The findings indicate a strong preference for fresh and large-sized prawns among the consumers. Income level substantially influenced the prawn purchases, with the high-income consumers more likely to buy premium prawn products, while the low-income consumers showed sensitivity to price changes. The primary concerns that significantly influenced the consumers’ purchasing decisions were found to be size, freshness, taste, price, market availability, and income. Additionally, the consumers’ perceived value and willingness-to-pay for prawns were significantly driven by size, freshness, environmental sustainability, and income levels. Policy recommendations include promoting sustainable prawn farming and improving accessibility for low-income consumers to enhance both nutritional intake and economic resilience. This research offers valuable insights for stakeholders in the prawn industry, facilitating the development of targeted marketing strategies and informed policymaking for sustainable industry growth.